Organic peroxides' gas-particle partitioning and rapid heterogeneous decomposition on secondary organic aerosol - H. Li; Chen, Z. M.; L.B. Huang; D. Huang (Atmospheric Chemistry and Physics, 2016)
Organic peroxides, important species in the atmosphere, promote secondary organic aerosol (SOA) aging, affect HOx radicals cycling, and cause adverse health effects. However, the formation, gas-particle partitioning, and evolution of organic peroxides are complicated and still unclear. In this study, we investigated in the laboratory the production and gas-particle partitioning of peroxides from the ozonolysis of a-pinene, which is one of the major biogenic volatile organic compounds in the atmosphere and an important precursor for SOA at a global scale. We have determined the molar yields of hydrogen peroxide (H2O2), hydromethyl hydroperoxide (HMHP), peroxyformic acid (PFA), peroxyacetic acid (PAA), and total peroxides (TPOs, including unknown peroxides) and the fraction of peroxides in a-pinene/O3 SOA. Comparing the gas-phase peroxides with the particle-phase peroxides, we find that gas-particle partitioning coefficients of PFA and PAA are 104 times higher than the values from the theoretical prediction, indicating that organic peroxides play a more important role in SOA formation than previously expected. Here, the partitioning coefficients of TPO were determined to be as high as (2–3)*104 m3 mg-1. Even so, more than 80% of the peroxides formed in the reaction remain in the gas phase. Water changes the distribution of gaseous peroxides, while it does not affect the total amount of peroxides in either the gas or the particle phase. Approx. 18% of gaseous peroxides undergo rapid heterogeneous decomposition on SOA particles in the presence of water vapor, resulting in the additional production of H2O2. This process can partially explain the unexpectedly high H2O2 yields under wet conditions. Transformation of organic peroxides to H2O2 also preserves OH in the atmosphere, helping to improve the understanding of OH cycling.